Dandy-Walker Malformation in an Asymptomatic 27-Year-Old Woman. A Case Report - Joyce Antonella Jiménez; Daniel Francisco Landívar; Fernando Xavier Posligua; Jorge Rigoberto González (University Library System, University of Pittsburgh, 2018)
Introduction: Dandy-Walker malformation (DWM) is a rare congenital disorder that involves the cerebellum and fourth ventricle. Incidentally detected asymptomatic DWM is sparsely reported in literature at extremes of age (from 1 to 75 years) in association with different diseases. We aim to report the case of a patient with an incidental finding of a DWM after a road traffic accident, reinforcing the importance of suspicion, investigation, diagnosis of clinical presentations. The Case: This case report describes a 27-year-old female patient who presented to the emergency room after a motor vehicle collision. She suffered a left kidney and spleen injury. The patient's brain CT scan revealed an enlarged cisterna magna with normal cerebellum, partial hypoplasia of the cerebellar vermis and enlargement of the fourth ventricle compatible with DWM. Neurological examination was unremarkable. An exploratory laparotomy was performed, and the left kidney and spleen showed hemorrhage, so a left nephrectomy and splenectomy was done. Conclusions: This case report aimed to characterize the DWM, which is a congenital malformation of the central nervous system. Asymptomatic patients do not require surgical treatment; however, these patients should be followed up once a year.